2012
DOI: 10.1186/1756-0500-5-335
|View full text |Cite
|
Sign up to set email alerts
|

Bullying among medical students in a Saudi medical school

Abstract: BackgroundBullying and sexual harassment of medical students by their teachers appears to be widespread phenomenon. However, nothing is published about its prevalence in conservative countries such as Saudi Arabia. This survey aims to ascertain the extent of these mistreatments among students in a Saudi medical school.FindingsA cross-sectional questionnaire survey was conducted on a group of 542 clinical years’ medical students in a Saudi medical school to explore students' perceptions of their educational env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
4
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 5 publications
4
45
4
11
Order By: Relevance
“…Since that time, studies conducted in different countries [1][2][3][4][5][6][7][8][9][10][11][12][13] have corroborated the high prevalence of different forms of aggression within medical education, thus giving support to the idea that these abusive situations reflect a strongly hierarchical medical culture.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since that time, studies conducted in different countries [1][2][3][4][5][6][7][8][9][10][11][12][13] have corroborated the high prevalence of different forms of aggression within medical education, thus giving support to the idea that these abusive situations reflect a strongly hierarchical medical culture.…”
Section: Introductionmentioning
confidence: 92%
“…In Saudi Arabia, Alzahrani 9 reported that the prevalence of bullying was 28% among medical students, whereas in Pakistan, the prevalence was 52% among sixth-year medical students. 6 In Colombia, Paredes et al 8 reported that the prevalence of bullying was 19.7%.…”
Section: Prevalence Of Exposure To Violencementioning
confidence: 99%
“…In 2012, Alzahrani21 reported that 28% of medical students reported perceiving some form of bullying during their clinical rotations. However, their study was limited to bullying from consultants, clinical professors, and tutors.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, although the rate of physical bullying decreases as individuals mature, indirect bullying is the preferred method at the university level. In her study Ozkal (2011) found that university students were mostly exposed to isolation and ideological bullying, and Alzahrani (2012) reported that verbal abuse and belittlement were more common that physical abuse among university students.…”
mentioning
confidence: 97%